Abnormal Cerebellar Development Is Involved in Dystonia-Like Behaviors and Motor Dysfunction of Autistic BTBR Mice - Xiao, Rui; Zhong, Hongyu; Li, Xin; Ma, Yuanyuan; Zhang, Ruiyu; Wang, Lian; Zang, Zhenle; Fan, Xiaotang (Frontiers in Cell and Developmental Biology, 2020)
Motor control and learning impairments are common complications in individuals with autism spectrum disorder (ASD). Abnormal cerebellar development during critical phases may disrupt these motor functions and lead to autistic motor dysfunction. However, the underlying mechanisms behind these impairments are not clear. Here，we utilized BTBR T+ Itprtf/J (BTBR) mice， an animal model of autism, to investigate the involvement of abnormal cerebellar development in motor performance. We found BTBR mice exhibited severe dystonia-like behavior and motor coordination or motor learning impairments. The onset of these abnormal movements coincided with the increased proliferation of granule neurons and enhanced foliation, and Purkinje cells displayed morphological hypotrophy with increased dendritic spine formation but suppressed maturation. The migration of granule neurons seemed unaffected. Transcriptional analyses confirmed the differential expression of genes involved in abnormal neurogenesis and revealed TRPC as a critical regulator in proliferation and synaptic formation. Taken together, these findings indicate that abnormal cerebellar development is closely related to dystonia-like behavior and motor dysfunction of BTBR mice and that TRPC may be a novel risk gene for ASD that may participate in the pathological process of autistic movement disorders.